PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP EFEKTIVITAS PEMUNGUTAN PENDAPATAN ASLI DAERAH PADA KABUPATEN SUBANG TAHUN 2019-2023 - Fairuz, Shania; Rohendi, Hendi (E-Jurnal Akuntansi TSM, 2025)
The effectiveness of local revenue (PAD) collection is very important for local governments to finance work programs in their regions and determine the level of regional independence. However, problems related to unachieved PAD are still found in various regions, one of which is Subang Regency. This study aims to measure the influence of the five dimensions of SPIP, both partially and simultaneously, on the effectiveness of PAD collection. The research method used is a quantitative method using a saturated sampling technique consisting of 11 OPDs collecting PAD and 52 respondents. Data collection techniques were carried out by distributing questionnaires, interviews, observations and data analysis and hypothesis testing using the SmartPLS 3 application. The results of this study indicate that partially the control environment, risk assessment, and monitoring influence the effectiveness of PAD collection, while risk assessment, information and communication do not influence the effectiveness of PAD collection. Furthermore, simultaneously SPIP has an influence on the effectiveness of PAD collection in Subang Regency.